Hubungan Pengetahuan, Sikap dan Kenyamanan Pekerja dengan Pemakaian Alat Pelindung Diri (APD) di Bengkel Las Listrik Kecamatan Amuntai Tengah Kabupaten HSU Tahun 2016 - Gusti Permatasari; Gunung Setiadi; Arifin Arifin (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: Relations Of Knowledge, Attitude And Comfort Of Personal Protective Equipment (PPE) In Las Electrical Workshop Subdistrict Central Amuntai Regency Hulu Sungai Utara 2016. Means work safety and health is one of the aspect protection of the labour to achieve optimal productivity. The means of the implementation of the safety and health of work, use of personal protection equipment (PPE) is a last choice in protecting the safety and health for workers of hazards potential. The results of a preliminary survey shows 60% on 10 workers of the las electrical workshop knowing the benefits and usefulness of the APD. The comfort factor of 80% felt less comfortable. The purpose of the study is to know the relations of knowledge, attitude and comfort with the use of personal protective equipment (PPE) in las electrical workshop Subdistrict Amuntai Central Regency Hulu Sungai Utara. The benefits of this research are as information materials and evaluation to find out the factors that affect its relationship with workers wearing of personal protection equipment (PPE). The research method used analytic survey with cross sectional design. Population of research to 40 people.Data analysis used X2 (Chi-Square). The results showed : (1) knowledge (p=0,000), (2) attitude (p=0,025), comfort (p = 0.002). The results showed that there is a relationship of knowledge, attitude and comfort with the use of personal protective equipment (PPE) in las electrical workshop Subdistrict Central Amuntai Regency Hulu Sungai Utara. An increase in oversight activities of las electrical workshops of workers so that workers work safely as wearing the of personal protective equipment (PPE) when working. Keywords: PPE; knowledge; attitude; comfort